2014
DOI: 10.2967/jnumed.113.135129
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of Brain White Matter Inflammation in Multiple Sclerosis with18F-PBR111 PET

Abstract: PET radioligand binding to the 18-kD translocator protein (TSPO) in the brains of patients with multiple sclerosis (MS) primarily reflects activated microglia and macrophages. We previously developed genetic stratification for accurate quantitative estimation of TSPO using second-generation PET radioligands. In this study, we used 18 F-PBR111 PET and MR imaging to measure relative binding in the lesional, perilesional, and surrounding normal-appearing white matter of MS patients, as an index of the innate immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
93
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 40 publications
8
93
1
1
Order By: Relevance
“…Significantly higher TSPO expression, measured with [ 11 C]PBR28 and PET, was recently found in cortical brain regions of patients with early onset Alzheimer's disease compared with subjects with mild cognitive impairment and healthy controls (22), which highlights the potential role of neuroinflammation in the etiology of Alzheimer's disease (6). However, studies examining TSPO expression between healthy control subjects and other patient groups such as multiple sclerosis, depression, or cocaine abusers (23)(24)(25)(26)(27) have produced mixed results. A well-established and robust preclinical model uses the administration of Escherichia coli lipopolysaccharide (LPS; also called endotoxin) to trigger "classic" activation of microglia and has been used in rodents to study neurodegeneration (28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Significantly higher TSPO expression, measured with [ 11 C]PBR28 and PET, was recently found in cortical brain regions of patients with early onset Alzheimer's disease compared with subjects with mild cognitive impairment and healthy controls (22), which highlights the potential role of neuroinflammation in the etiology of Alzheimer's disease (6). However, studies examining TSPO expression between healthy control subjects and other patient groups such as multiple sclerosis, depression, or cocaine abusers (23)(24)(25)(26)(27) have produced mixed results. A well-established and robust preclinical model uses the administration of Escherichia coli lipopolysaccharide (LPS; also called endotoxin) to trigger "classic" activation of microglia and has been used in rodents to study neurodegeneration (28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Second generation TSPO radioligands such as [ 11 [142][143][144]. Increased [ 18 F]PBR111 binding has been found in MS lesions and in perilesional white matter (WM) volumes of MS patients compared to healthy controls [144].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Human studies using these secondgeneration ligands have demonstrated increased TSPO expression in a variety of CNS disorders, including Alzheimer's disease [37], amyotrophic lateral sclerosis [34], and multiple sclerosis [38].…”
Section: Challenges Of Second-generation Tspo Pet Radioligandsmentioning
confidence: 99%